DEVELOPMENT OF DIGITAL MARKETING OF BANKING INSTITUTIONS - NIANKO, Liudmyla; NIANKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article draws attention to the issues of development of the system of digital banking services in Ukraine, in particular in terms of marketing and direct promotion of digital services of banking institutions. Therefore, the purpose of the study is to improve the methodological and applied principles and provisions for the promotion of digital banking services of banking institutions.It is shown that new economic conditions and realities have increased competition in the banking sector, which, in turn, prompts banking institutions to search for new sources of efficiency and intensify their own development through better promotion of banking services through new sales channels. One of these directions is, firstly, the marketing itself, and, secondly, the provision of digital banking services. It has been established that the development of digital marketing of banking institutions is due in equal measure to two trends: the digital transformation of the economy and society, and, therefore, the increase in the level of demand of consumers of banking products for their service online and/or with the use of the Internet; the development of digital networks and communications, and, therefore, a significant expansion of technical, technological and even economic opportunities for the implementation of digital technologies in the activities of banking institutions.The stages of the development process of digital technologies in the activities of banking institutions were identified, which went through 5 evolutionary stages - from the appearance of digital channels to the creation of "digital DNA" - a new system of coordinates for making strategic decisions throughout the entire life cycle of the operation and development of a banking institution.The leading directions and advantages of implementing the tasks of the digital marketing strategy of banking institutions have been determined, which are: modernization of the communication system with clients, significant growth of opportunities in the volume of communications and in the subjects of "communication"; a significant increase in the capabilities of the information and analytical subsystem of marketing, which is the way to make more reasonable and reliable management decisions in the field of marketing management; increasing the economic efficiency of the provision of banking services, increasing their scale and efficiency both vertically and horizontally in the business technological process; expansion of opportunities for the implementation of image programs, increasing the level of customer loyalty and their trust in the bank and its banking services.The leading directions of the development of digital marketing of banking institutions are indicated, which define the corporatization of digital systems of business communications and the provision of banking services, the use of digital marketing opportunities to increase the volume of provision of basic and additional services on the Internet, the spread of digital marketing to the intrabank management system, its automation.
Keywords: digital technologies; digitalization; marketing; Internet marketing; digital communications; banking institutions